2012
DOI: 10.5664/jcsm.2032
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Quality of Sleep on Recovery from Fast-Track Abdominal Hysterectomy

Abstract: cepts to improve sleep postoperatively 1 ; it was only recently that Krenk et al. suggested that prophylactic intervention to improve sleep architecture be included in fast-track methodology. 3 The impact of surgery and anesthesia on postoperative sleep after hysterectomy in a fast-track setting has not been carefully Study Objectives: To examine the impact of mode of anesthesia on perceived quality of sleep and to analyze the perceived quality of sleep in affecting recovery from surgery. Methods: A randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 18 publications
3
59
0
2
Order By: Relevance
“…One study generated five separate citations, which were treated as one unique study. [18][19][20][21][22] The majority of studies (67%) were controlled trials [37 randomized controlled trials (RCTs) and one non-randomized controlled trial]. Of the remaining studies, 14 (25%) were controlled before-after studies, five (9%) were retrospective cohort studies, and one (2%) was a prospective cohort study.…”
Section: Resultsmentioning
confidence: 99%
“…One study generated five separate citations, which were treated as one unique study. [18][19][20][21][22] The majority of studies (67%) were controlled trials [37 randomized controlled trials (RCTs) and one non-randomized controlled trial]. Of the remaining studies, 14 (25%) were controlled before-after studies, five (9%) were retrospective cohort studies, and one (2%) was a prospective cohort study.…”
Section: Resultsmentioning
confidence: 99%
“…Abdominal hysterectomy under spinal anesthesia offered significantly better quality of sleep than did general anesthesia, which led to a significantly shorter stay in the hospital. However, this effect was almost exclusively attributed to a significantly lower consumption of opioids postoperatively in the spinal anesthesia group (60).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have closely examined the phenomenon of postoperative first‐night sleep disturbance (PFSD) . Several studies have focused on comparing epidural and paravertebral blockade techniques in pain management after thoracotomy .…”
Section: Discussionmentioning
confidence: 99%
“…12,[14][15][16][17][18][19] Recent studies have closely examined the phenomenon of postoperative first-night sleep disturbance (PFSD). [20][21][22] Several studies have focused on comparing epidural and paravertebral blockade techniques in pain management after thoracotomy. [23][24][25] However, none of these studies reported on the sleep quality of the participants.…”
Section: Discussionmentioning
confidence: 99%